Enhancing Healthcare Facility in Rural Areas Using Internet of Things (IoT) - Cae-Li, Chiew; Kumar Appadurai, Naresh; Shanmugam, Kamalanathan (International Journal of Psychosocial Rehabilitation, 2019)
Internet of Things (IoT) in recent years, facilitates in revolutionizing the introduction, and acceptance of healthcare facilities in rural areas. IoT offers a more efficient way to access healthcare and at the same time better manages the cost of implementing it. The main usage of IoT in healthcare is monitoring patients’ health conditions without having being required to be physically present. As powerful as IoT may sound, it also comes with many security challenges as well as using energy efficiently. A number of research papers have proposed multiple ways of handling these challenges and the different types of sensors used in these IoT devices. After thorough research, a combined analysis of health data recorded in several countries have also been reviewed to aid in identifying the requirements of patients especially those in remote areas. The aim of this research is to give an insight on how IoT usage in healthcare is able to revolutionize the entire industry, moving on from its traditional ways of caring for patients. This research paper is a compilation of different viewpoints of IoT in healthcare from different papers, explaining in detail why and how IoT is used in this industry and the steps taken to mitigate the challenges faced